Aiming trajectories of the sight in the German Archery - Ganter, N.; Link, D.; Heller, M.; Edelmann-Nusser, J. (World Congress of Performance Analysis of Sport VIII, 2008)
With the described video based system it is possible to measure aiming movements of the bow in the competition situation. From the movement trajectories of the sight individual specific aiming strategies and their intraindividual stability can be identified. Regarding the extent of the movements, results of previous studies using a different measuring system in the training situation (Edelmann-Nusser et al., 2002; 2006), which showed larger aiming movements in the horizontal direction, could be confirmed. Interestingly, no differences could be observed for the extent of the aiming movement when comparing male to female archers, who both shot in the competition under the same conditions. The results of the averaged shooting ends suggest that small movements of the bow are positively related to a high score. However, this can not be completely confirmed, since scores in the competition are not available on a shot-to-shot basis. So, one can state that a small aiming movement is advantageous for - but does not inevitably lead to - a high score. Moreover, further influences on the stability of the aiming movements during the competition, like muscular fatigue or changing wind conditions require further analysis. Since the trajectory of the sight is only tracked in two dimensions, there are some limitations in reference to the real movement of the aim point on the target, that may be caused by tilting movements of the bow and combined translational and rotational movements while aiming. Nevertheless, the system provides valuable information on the aiming movements in the competition situation, making it a useful tool for analyzing high-level archery performance and for supporting the training process.